Dosimetric effects of the supine and prone positions in proton therapy for prostate cancer - Takahiro Kato; Masato Kato; Kimihiro Takemasa; Masao Murakami (Journal of Medical Physics, 2022)
Purpose: To quantitatively evaluate how much the doses to organs at risk are affected in the prone position compared to the supine position in the proton therapy (PT) for prostate cancer. Materials and Methods: Fifteen consecutive patients with clinically localized prostate cancer underwent treatment planning computed tomography scans in both the supine and prone positions. The clinical target volume (CTV) consisted of the prostate gland plus the seminal vesicles. The PT plans were designed using the standard lateral opposed fields with passively scattered proton beams for both treatment positions. The prescribed dose for each plan was set to 78 Gy (Relative biological effectiveness)/39 fractions to 50% of the planning target volume. Dose-volume metrics of the rectum and bladder in the two treatment positions were analyzed. Results: It was confirmed that all the parameters of D05, D10, D20, D30, Dmean, and V90 examined in the rectum were significantly reduced in the prone position. There was no significant difference between the two positions in the bladder dose except for Dmean. The distance between the CTV and the rectum tended to increase with the patient in the prone position; at the prostate level, however, the maximum change was approximately 5 mm, and there was significant variation between cases. Conclusions: We confirmed that the rectal doses were significantly lower in the prone compared with the supine position in PT. Although uncertain, the prone position could be an effective method to reduce the rectal dose in PT.